108: FLUORESCENCE ANGIOGRAPHY IN COLONIC INTERPOSITION AS RECONSTRUCTION AFTER ESOPHAGEAL RESECTION. (23rd April 2022) - Joosten, H; Gisbertz, S; Eshuis, W; Heineman, D; Daams, F; Van Berge Henegouwen, M
Abstract: Background and aim: Colonic interposition is an alternative for gastric conduit reconstruction after esophagectomy. Postoperative anastomotic leakage occurs in 15–30% of the patients and may partially be attributed to reduced blood supply to the colon and ileum after vascular ligation. Fluorescence angiography (FA) can visualize tissue perfusion and guide the surgeon in selecting the anastomotic site. We aimed to give an overview of the postoperative outcomes and the first experiences of FA in colonic interposition. Methods: This cohort study included all consecutive patients who underwent a colonic interposition between January 2015 and February 2021 in the Amsterdam UMC. Colonic interposition was performed for three different indications: inability to use the stomach because of previous gastric surgery or extensive tumour involvement, cancer recurrence in the gastric conduit requiring resection or because of complications after initial esophagectomy with failure and resection of the gastric conduit (i.e. ischaemia). Since 2018 FA was performed prior to anastomotic reconstruction by administration of indocyanine green (ICG) injection (0.1 mg/kg/bolus). Imaging was performed by hand-held Spy-phi (Stryker, Kalamazoo, MI, U.S.A.). Results: Twenty six patients were included(18 male, mean age 64), of whom thirteen (50%) underwent intra-operative FA assessment. Within the FA group two (15%) cervical anastomotic leakages occurred, whereas in the non FA group two anastomotic leakages and one graft necrosis (19%) occurred ( P  = 0.61). There was a change of management due to the FA assessment in two patients in the FA group (15%) which lead to a more extensive resection. In both cases no anastomotic leakage occurred. Mean ± SD operative time in the FA group versus the non FA group was 375 ± 87 versus 400 ± 112 minutes respectively ( P  = 0.56). Conclusion: This is the first study that shows the potential role of FA enabling the surgeon to intra-operatively optimize perfusion in colonic interpositions. Further research is warranted to better elucidate this role.